A Divisible Search Model of Fiat Money - Shouyong Shi (Queen's University, Department of Economics, 1996)
This paper extends the Kiyotaki-Wright search model of fiat money to allow for divisible money and goods. The extension allows me to examine the standard issues in monetary economics, such as the neutrality and super-neutrality of money, by severing the artificial link in the Kiyotaki-Wright model between the money supply and the number of money holders. It is shown that money is neutral, but not super-neutral. Money growth generates a trading opportunity effect: it changes the fraction of different agents in the economy and hence changes the probability with which agents have a successful match. In addition, money growth has a negative effect on the real money balance that is familiar in Walrasian monetary models. The balance of the two effects can imply a positive optimal money growth rate.
Keywords: 330; search; fiat money; neutrality; super-neutrality; trading opportunity; coincidence of wants